2021
DOI: 10.1108/ijoes-05-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Environmental quality awareness, green trust, green self-efficacy and environmental attitude in influencing green purchase behaviour

Abstract: Purpose The purpose of this study is to examine the effect of green trust (GT), environmental quality awareness (EQA), green self-efficacy (GSE) and environmental attitude (EA) towards green purchase behaviour (GPB). The mediating effect of EA is also investigated. Design/methodology/approach Attribution theory and the attitude-behaviour gap model were used to develop the research model. Data were collected through an online survey, which yielded 321 complete and usable responses. The partial least square-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 112 publications
5
22
0
3
Order By: Relevance
“…The findings indicate that the internal deliberative processes consumers undertake before a possible purchase of green apparel can positively influence their intentions. The findings, moreover, align with previous research, which has identified attitude (Dhir et al, 2021;Yadav & Pathak, 2016), self-efficacy (Ahmad et al, 2022;Pang et al, 2021) and personal norms (Jaini et al, 2020;Shin et al, 2018) as significant cognitive factors inducing proenvironmental behaviour. These findings represent a key contribution in the context of the USA because they explain the consumption patterns for green and sustainable products in this economy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings indicate that the internal deliberative processes consumers undertake before a possible purchase of green apparel can positively influence their intentions. The findings, moreover, align with previous research, which has identified attitude (Dhir et al, 2021;Yadav & Pathak, 2016), self-efficacy (Ahmad et al, 2022;Pang et al, 2021) and personal norms (Jaini et al, 2020;Shin et al, 2018) as significant cognitive factors inducing proenvironmental behaviour. These findings represent a key contribution in the context of the USA because they explain the consumption patterns for green and sustainable products in this economy.…”
Section: Discussionsupporting
confidence: 89%
“…As with attitude, scholars have previously investigated and found efficacy to positively influence individuals' pro-environmental behaviours and intentions (Bopp et al, 2019;Wang, Zhang, et al, 2019). For example, Sh. Ahmad et al (2022) found green self-efficacy to significantly influence green purchase behaviour, while Pang et al (2021) found self-efficacy to predict organic food purchase intentions.…”
Section: Organism-responsementioning
confidence: 99%
See 1 more Smart Citation
“…(2021) found that consumer-oriented drivers are critical in forming consumer trust in green products. Ahmad et al (2022) confirmed a positive effect of green trust on green product purchase intention and behavior. However, whether these relationships and effects hold in an online shopping setting are unclear.…”
Section: Online Green Trustmentioning
confidence: 55%
“…As most people desire to undertake activities that are compatible with their views, laws, and social duties, self-efficacy is connected with several behavioral outcomes such as participation and persistence. (Chen et al, 2014:6608), (Ahmad et al, 2021), (Sharma & Dayal, 2016) explained Self-efficacy increases intrinsic motivation that leads to pro-environmental behavior. According to this concept, self-efficacy represents the beliefs related to the ability of organizations to work to reduce environmental degradation, which helps them to understand the special ability related to organizing and directing the course of environmental action that aims to lead a positive environmental behavior.…”
Section: Study Objectivesmentioning
confidence: 99%